2012
DOI: 10.1590/s0100-736x2012001300003
|View full text |Cite
|
Sign up to set email alerts
|

Parâmetros hemogasométricos e equilíbrio ácido-básico de cabritos nascidos de partos normais

Abstract: RESUMO.-A adaptação à vida extra-uterina é período críti-co para o recém-nascido. Inúmeras alterações ocorrem em diferentes sistemas e órgãos, incluindo a função respirató-ria e o equilíbrio ácido-básico. O presente trabalho objetivou constatar a ocorrência de acidose em cabritos recém--nascidos e obter parâmetros gasométricos e ácido-básicos dos mesmos, até as 24 horas de vida. Para tanto, foram utilizados 33 cabritos, sem distinção de sexo. Amostras san- The extra-uterine life adaptation is a critical period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The level of hypoxia and acidosis may vary depending on the onset of spontaneous breathing and the time it takes for the mother to completely leave the fetal bloodstream (Reece, 2004). It has been reported that there is no significant difference in pH, pCO2, pO2 and HCO3 levels at 0 and 24 hours in calves with dystocia compared to calves with eutocia (Feitosa et al, 2012). In another study, it was found that foals and lambs born as a result of dystocia had low pH and HCO3 levels, and the improvements in blood gases were similar on the 1st day, according to those results, it was reported that in foals born as a result of dystocia there were negative effects on blood gases (Aydoğdu et al, 2018;Kimura et al, 2017).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The level of hypoxia and acidosis may vary depending on the onset of spontaneous breathing and the time it takes for the mother to completely leave the fetal bloodstream (Reece, 2004). It has been reported that there is no significant difference in pH, pCO2, pO2 and HCO3 levels at 0 and 24 hours in calves with dystocia compared to calves with eutocia (Feitosa et al, 2012). In another study, it was found that foals and lambs born as a result of dystocia had low pH and HCO3 levels, and the improvements in blood gases were similar on the 1st day, according to those results, it was reported that in foals born as a result of dystocia there were negative effects on blood gases (Aydoğdu et al, 2018;Kimura et al, 2017).…”
Section: Discussionmentioning
confidence: 95%
“…Newborn lives are sensitive to adverse environmental conditions and perinatal diseases, and their metabolic status is highly variable (Piccione et al, 2007). During this period, numerous changes occur in different systems and organs, including respiratory function and acid-base balance (Camargo et al, 2012). Newborns may die due to trauma and prolonged hypoxia during delivery (Feitosa et al, 2012).…”
mentioning
confidence: 99%
See 1 more Smart Citation